Public health challenges and emerging diseases: the case of São Paulo - Luiz Jacintho da Silva
The author discusses the challenges posed by emerging infectious diseases in 100 years of public health in the state of São Paulo, Brazil. With an advanced and organized public health system, São Paulo responded to the emergence of infectious diseases by creating research institutions and control programs. The late 19th century witnessed the first modern research institution in microbiology, in response to the bubonic plague. A changing economy led to constant changes in ecosystems. The late 20th century presents a wide array of both emerging and rapidly changing infectious diseases. The present situation calls for creative solutions. Ecosystem analysis and more agile epidemiological surveillance are seen as the best alternatives.